2017
DOI: 10.1016/j.jclepro.2017.09.114
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the generation of economic results in the different phases of the pro-environmental change process

Abstract: Analysis of the generation of economic results in the different phases of the pro-environmental change process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 56 publications
(85 reference statements)
2
18
0
1
Order By: Relevance
“…The term eco-innovation is commonly associated with the development of new ecological products, the consumption of renewable or more sustainable sources and the reduction of waste through technological innovation based on or pursuing eco-efficiency [4], which was derived from the search for an increase in competitiveness through environmental improvement [5]. In fact, the increasing importance of environmental issues for companies can be driven through eco-innovation, generating competitive advantages [6] and, ultimately, economic and environmental efficiency [7].…”
Section: Introductionmentioning
confidence: 99%
“…The term eco-innovation is commonly associated with the development of new ecological products, the consumption of renewable or more sustainable sources and the reduction of waste through technological innovation based on or pursuing eco-efficiency [4], which was derived from the search for an increase in competitiveness through environmental improvement [5]. In fact, the increasing importance of environmental issues for companies can be driven through eco-innovation, generating competitive advantages [6] and, ultimately, economic and environmental efficiency [7].…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that regional policies should be analyzed to allow for the creation of indicators that are closer to reality. Some of these indicators were included in the instruments proposed for the measurement of eco-innovation [25,26,35,40,42,58].…”
Section: Results: Proposed Model Factorsmentioning
confidence: 99%
“…When analyzing the factors that drive eco-innovation, one of the most important factors considered is environmental regulations [30][31][32][33]. In Europe, for example, it has been a determining factor for the development of industries that manage natural resources [34]; previously, they were considered an imposition for companies, but the thinking has changed and today they are considered favorable when innovating, since they help companies to identify efficiency failures in their processes and are used as a tool to reduce default and production costs, improving competitiveness [35,36]. The companies discovered that by investing financially in eco-innovation activities, their competitive advantage also increased [37,38], bringing benefits such as cost savings, improved corporate image, marketing advantages, sustainable growth in the environment, and creation of new markets [13,14].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Barney (1986) propõe que o uso de determinadas estratégias convergentes com determinados posicionamentos pode gerar vantagens competitivas para as organizações. Complementarmente, Albertini (2013) e Scarpellini et. al (2017) identificaram que questões de ordem ambiental são itens essenciais para a manutenção de uma cultura organizacional competitiva, argumento que já era defendido por Elkington (1997).…”
Section: Discussõesunclassified